Les sociétés humaines face aux changements climatiques. - Djindjian, François (Union Internationale des Sciences Préhistoriques et Protohistoriques., 2022)
Is climate change a factor of change for human societies that can be witnessed through time, forcing them to adapt and find sustainable solutions? This book is the second of two volumes exploring human societies facing climate change in pre and protohistory. Volume 2 concerns protohistory, from the beginning of the Holocene to historical times.